THE IMPACT OF HALAL COMPLIANCE ON CONSUMER SATISFACTION IN THE COSMETIC INDUSTRY - Wibawa, Berto Mulia; Safira, Anya (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2024)
This study investigates the impact of halal certification, business legality, and brand image on consumer trust and satisfaction in the cosmetic industry. With a focus on female consumers in Indonesia, the research employs a quantitative approach using purposive random sampling. Data was collected through questionnaires distributed via social media and analyzed using SmartPLS. The findings indicate that halal certification, business legality, and brand image positively influence consumer trust, which in turn significantly affects consumer satisfaction. Moreover, halal certification and brand image directly enhance customer satisfaction, underscoring the importance of these factors in fostering positive consumer perceptions and experiences. This research highlights the critical role of religious compliance, legal adherence, and strong brand identity in building consumer trust and achieving high levels of satisfaction in the competitive cosmetic market. Limitations of the study include its geographical focus on Indonesia and the reliance on self-reported data, suggesting avenues for future research to explore these relationships in different cultural contexts and using diverse methodologies.